Penanggulangan Stunting Melalui Sosialisasi dan Edukasi Gizi Seimbang di Desa Tambang, Kabupaten Ponorogo, Jawa Timur - Tamara Adelia Nainggolan; Indri Pramudita; Adhinugraha Wirayudha Kusuma; Radja Alzeron Rizaldy; Christia Meidiana; Astrida Fitri Nuryani (Sekolah Tinggi Pastoral Kateketik Santo Fransiskus Assisi, 2023)
Stunting has become a serious health problem in Indonesia as it is associated with failure to thrive, brain development disorders, decreased mental abilities, poor health conditions, and low socio-economic capabilities. In 2020, the United Nations recorded that around 6.3 million Indonesian early childhood or toddler aged children experienced stunting, caused by nutritional deficiencies within the first two years of their lives, maternal malnutrition during pregnancy, and poor sanitation. Through the